ALDEHID DEHIDROGENASE DALAM TIKUS WISTAR SEBAGAI BIOMARKER AWAL KONSUMSI ALKOHOL SECARA AKUT - SUANITI, NI MADE; DJELANTIK, A.A.GEDE SUDEWA; SUASTIKA, I KETUT; ASTAWA, I NYOMAN MANTIK (Jurnal Biologi Udayana; Vol 15 No 1 (2011): Jurnal Biologi, 2011)
Research on oral consumption of alcohol on rat Wistar was done to examine level of aldehyde dehydrogenase (ALDH) in rat serum. The research design was true randomized experimental post test only control group design. This research was conducted in two stages: first, eight rats were treated with 5% alcohol continuously for 1 week and as control aquadest was given to eight rats. The second stage was determination of ALDH levels. Wistar rat serum were taken after 6 hours and 24 hours of 5% alcohol consumption. The levels of ALDH increase by 117.15% after 6 hours of 5% alcohol consumption, while after 24 hours the levels of ALDH increase by 108.14%. ALDH levels in serum rat Wistar can be used as early biomarker of acute alcohol consumption.
Keywords: ALDH; histopathology; rat Wistar; biomarker; alcohol